2008
DOI: 10.1161/circulationaha.108.780734
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Older Thrombus Is an Independent Predictor of Long-Term Mortality in Patients With ST-Elevation Myocardial Infarction Treated With Thrombus Aspiration During Primary Percutaneous Coronary Intervention

Abstract: Background-Routine thrombus aspiration is frequently used during primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction to prevent distal embolization. Recently, evidence of clinical benefit was published. In 50% of the ST-elevation myocardial infarction patients with an onset of symptoms Ͻ12 hours before, thrombi were shown to be Ͼ1 day old. This observation illustrates that plaque rupture and coronary occlusion are significantly separated in time. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 20 publications
(23 reference statements)
5
100
1
Order By: Relevance
“…The results of histopathological evaluations of aspirated intracoronary thrombi obtained from STEMI patients have recently been presented [73][74][75][76][77] . Rittersma et al investigated 199 aspirated intracoronary thrombi obtained from STEMI patients within six hours of symptom onset and pathologically classified them into fresh thrombi (<1 day old) composed of layered patterns of fibrin and intact platelets, erythrocytes and granulocytes and older thrombi with lytic (1 to 5 days) or organized (>5 days) changes 73) .…”
Section: Pathological Analysis Of Aspirated Intracoronary Thrombimentioning
confidence: 99%
See 2 more Smart Citations
“…The results of histopathological evaluations of aspirated intracoronary thrombi obtained from STEMI patients have recently been presented [73][74][75][76][77] . Rittersma et al investigated 199 aspirated intracoronary thrombi obtained from STEMI patients within six hours of symptom onset and pathologically classified them into fresh thrombi (<1 day old) composed of layered patterns of fibrin and intact platelets, erythrocytes and granulocytes and older thrombi with lytic (1 to 5 days) or organized (>5 days) changes 73) .…”
Section: Pathological Analysis Of Aspirated Intracoronary Thrombimentioning
confidence: 99%
“…Several recent studies have demonstrated associations between coronary thrombus characteristics and DE/myocardial perfusion 46,47,77,78,84) , restenosis 80) , the left ventricular (LV) function/remodeling 77,78) and long-term mortality 75) (Table 2).…”
Section: Coronary Thrombus Components and Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Along with the clinical benefits of thrombus aspiration, retrieval of atherothrombotic material provides us with new possibilities to study the pathophysiology of thrombus formation, and thrombus characteristics may become of value in predicting outcome. In this issue of Circulation, Kramer et al 15 identify the age of aspirated thrombus as a predictor of long-term mortality in patients with STEMI treated with thrombus aspiration during primary PCI. Previously, these investigators have reported that in many STEMI patients who underwent thrombus aspiration during primary PCI within 6 hours of symptom onset, at least part of the thrombotic material was older than 1 day.…”
Section: Article P 1810mentioning
confidence: 99%
“…15 The platelet fresh component of the thrombus is unstable and prone to embolization into the distal microcirculation, causing MVO and interstitial inflammatory damage. 16 The embolism that occurs several days before the onset of symptoms was recently suggested by In the infarcted wall, MVO could impede coronary blood ejection into the venous circulation and could therefore cancel the benefit conferred in certain cases by coronary collateralization.…”
Section: Discussionmentioning
confidence: 99%